Italy : Selected Issues. (IMF Staff Country Reports; Country Report, 2000)
The paper examines macroeconomic and structural factors potentially explaining the country's underperformance. A comparison between the reform and baseline policy scenarios underscores maintaining a strong fiscal position, early reductions in primary expenditures, and reducing fiscal vulnerability. Assigning the financing and management of the health care system to the regions may increase the efficiency and the productivity of the health care system. The information on Italy's economy and legal as well as regulatory environment is available on the worldwide web, and the paper lists the related sites.